Effect of Ultrasound Therapy on Patients With Osteoarthritis of The Knee Joint (KYAMC Journal, 2017)
Background: Osteoarthritis (OA) is the most common form of arthritis accounting for about 30% of general physician visits. Objectives: To detect the effects of ultrasound therapy on patients with osteoarthritis of the knee joint.Methodology: It was a prospective non randomized clinical study, conducted in the Department of Physical Medicine and Rehabilitation, Bangabandhu Sheikh Mujib Medical University, Shahbagh, Dhaka during the periods of 1st March, 2012 to 31st August, 2012. Fifty four patients between 35-75 years of age without consideration of gender with a history of not less than three months knee pain with radiographic confirmation of primary osteoarthritis were selected purposefully. Then they were divided randomly in group A & group B. Group A received g NSAID [Aceclofenac 100mg B.D.-10 days]+Omeprazol (20mg B.D.-10days) + Therapeutic exercise + ADL and Group B received gUST+NSAID [Aceclofenac 100mg B.D.-10 days]+ Omeprazol (20mg B.D.-10days) + Therapeutic exercise + ADL. In both groups the patients were observed for six weeks. Outcome measured by VAS, ROM, 50 feet walking time and WOMAC index.Results: Mean ± SD of age in group A and group B were 52.33 ± 9.62 years and 52.29 ± 9.67 years respectively. Among the 27 patients in group A 9 (33.3%) were male and 18 (66.7%) were female. Among the 27 patients in group B 10 (37.0%) were male and 18 (63.0%) were female. Mean ± SD of VAS during pre treatment in group A and group B were 6.22 ± 1.60 and 7.15 ± 1.56 respectively. Mean ± SD of ROM during pre treatment in group A and group B were 117.33 ± 13.05 and 112.37 ± 19.01 respectively. Mean ± SD of time taken to walk 50 feet during pre treatment in group A and group B were 18.22 ± 2.39 and 18.81 ± 2.13 minutes respectively. Mean ± SD of WOMAC index in group A and group B were 60.85 ± 15.86 and 67.33 ± 16.33 minutes respectively. After treatment in both groups VAS, time taken to walk 50 feet and WOMAC index gradually decreased and ROM gradually increased.Conclusion: Although the study conducted with small sample size in a single centre in Dhaka city which may not be representative for the whole country it was found that there was statistically significant difference found in VAS, ROM, and time taken to walk 50 feet and WOMAC index between the groups.KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 750-757